Description of a new species of Xyletinus Latreille, 1809 from South Kazakhstan with a note on Xyletinus (Xeronthobius) desertus (Barovskij, 1929) (Coleoptera: Ptinidae: Xyletininae) - A.V. Kovalev; A.M. Shapovalov (Кавказский энтомологический бюллетень, 2015)
A new species Xyletinus (Xeronthobius) aralensis sp.  n. from South Kazakhstan (Kyzylorda Region) is described. A new synonymy is established: X. (Xeronthobius) desertus (Barovskij, 1929)  = X. (X.) kozlovi Emetz in Emetz et Logvinovskij, 1977, syn. n.